PENGARUH LAYANAN KONSELING KELOMPOK TEKNIK COGNITIF BEHAVIOR THERAPY (CBT) TERHADAP KECEMASAN AKADEMIK SISWA KELAS XI SMAS AL-WASHLIYAH 3 MEDAN TA 2025/2026 - Dwi Silvia Zakiah Sarinta Siregar; Nur Asyah; Khairina Ulfa Syaimi; Nurul Azmi Saragih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Academic anxiety is an emotional condition characterized by the fear, worry, and tension that students experience in dealing with academic situations such as exams, assignments, or teacher assessments. This research aims to find out the influence of group counseling services of cognitive behavior therapy (cbt) techniques on the academic anxiety of students of class XI of Al-Washliyah 3 Medan. Group counseling services with a cognitive behavior therapy (cbt) approach plays an important role in emphasizing the relationship between thoughts, feelings and behaviors and assisting individuals in changing the rational mindset. This research uses a quantitative approach with the design of one group pretest-posttest design with the help of the SPSS version 20 for windows program. The population in the study amounted to 50 students and the sample was taken purposive sampling as many as 10 students who had high academic anxiety. Based on the results of the calculation of the test of the data analysis hypothesis there is an average value of pre-test which is 126.30 while the average score of the post-test 94.80 of the data shows that academic anxiety decreased by 31,500. thus it can be concluded that this intervention is effective in helping students reduce academic anxiety experienced. This finding is expected to be a reference for BK teachers in designing group counseling services that are appropriate to reduce students’ academic anxiety in schools.